2022
DOI: 10.3390/bioengineering9040140
|View full text |Cite
|
Sign up to set email alerts
|

Is It Possible to Improve Urinary Incontinence and Quality of Life in Female Patients? A Clinical Evaluation of the Efficacy of Top Flat Magnetic Stimulation Technology

Abstract: Background and Objectives: Urinary incontinence is the accidental loss of urine that can occur at any age, especially among women over 50; however, its prevalence is increasing. This study aimed to assess the efficacy and safety of a device that uses Top Flat Magnetic Stimulation for the management of women with mixed urinary incontinence. Materials and Methods: A total of 50 female patients underwent a total of six treatment sessions performed twice a week for three consecutive weeks, for 28 min. Three questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…In the case of pelvic floor muscle hypertonic dysfunction, many non-invasive techniques are available. Physiotherapy is the first-line conservative therapy but has the disadvantage of having slow progression and low patient adherence and compliance with treatment [ 49 , 50 ]. The same thing can be said for Kegel exercises, whose effectiveness is reduced because they are often performed inconsistently or incorrectly over time by patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of pelvic floor muscle hypertonic dysfunction, many non-invasive techniques are available. Physiotherapy is the first-line conservative therapy but has the disadvantage of having slow progression and low patient adherence and compliance with treatment [ 49 , 50 ]. The same thing can be said for Kegel exercises, whose effectiveness is reduced because they are often performed inconsistently or incorrectly over time by patients.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lopopolo et al reported a significant improvement in quality of life and patients awareness of the pelvic floor area in 50 women with mixed urinary incontinence treated with six sessions of FMS even at the end of the treatment and at three months follow-up. In addition, at the baseline evaluation, patients most frequently experienced leakage several times a day, whereas after six sessions, the leakage occurred only about once a week or less [ 44 ]. Biondo et al evaluated the effectiveness and safety of flat magnetic stimulation in eighty-one female patients (35 patients who reported SUI symptoms and 46 patients who reported UUI symptoms) after eight 28 min treatment sessions (twice a week for 4 weeks).…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires were completed right before every treatment, within the treatment period (until the 8th session). To assess SUI, the Urinary Incontinence Short Form (ICIQ-UI-SF), [ 6 , 22 ] was used to assess the severity of urinary leakage, the clinical manifestations of urinary incontinence, and the impact on quality of life. Moreover, the seven-question Incontinence Impact Questionnaire-Short Form (IIQ-7) [ 23 ] was helpful to evaluate the negative impacts of urinary incontinence on health-related quality of life in terms of physical activities, recreation, domestic tasks, social activities, travelling, emotional health and the sensation of frustration [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence ranges from 17% in women in their 20s to 38% in their 60s [ 4 ]; however, only 25% of patients seek specific medical treatment [ 5 ]. For this reason, in the last decade, many strategies have been investigated for treating UI [ 6 , 7 ]. They are surgical procedures, physical/conservative therapies (pessaries or vaginal cones, timing urination and restricting fluid intake), pharmacological approaches (anticholinergic drugs, urethral bulking agents, vaginal oestrogens and peripheral nerve stimulation), and behavioural therapies (Kegel exercises, vaginal weight training, biofeedback and electrical stimulation of pelvic floor) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation